CXCL12/SDF-1 facilitates optic nerve regeneration - Annemarie Heskamp; Marco Leibinger; Anastasia Andreadaki; Philipp Gobrecht; Heike Diekmann; Dietmar Fischer (Neurobiology of Disease, 2013)
Mature retinal ganglion cells (RGCs) do not normally regenerate injured axons, but undergo apoptosis soon after axotomy. Besides the insufficient intrinsic capability of mature neurons to regrow axons inhibitory molecules located in myelin of the central nervous system as well as the glial scar forming at the site of injury strongly limit axon regeneration. Nevertheless, RGCs can be transformed into a regenerative state upon inflammatory stimulation (IS), enabling these neurons to grow axons into the injured optic nerve. The outcome of IS stimulated regeneration is, however, still limited by the inhibitory extracellular environment. Here, we report that the chemokine CXCL12/SDF-1 moderately stimulates neurite growth of mature RGCs on laminin in culture and, in contrast to CNTF, exerts potent disinhibitory effects towards myelin. Consistently, co-treatment of RGCs with CXCL12 facilitated CNTF stimulated neurite growth of RGCs on myelin. Mature RGCs express CXCR4, the cognate CXCL12 receptor. Furthermore, the neurite growth promoting and disinhibitory effects of CXCL12 were abrogated by a specific CXCR4 antagonist and by inhibition of the PI3K/AKT/mTOR-, but not the JAK/STAT3-pathway. In vivo, intravitreal application of CXCL12 sustained mTOR activity in RGCs upon optic nerve injury and moderately stimulated axon regeneration in the optic nerve without affecting the survival of RGCs. Importantly, intravitreal application of CXCL12 also significantly increased IS triggered axon regeneration in vivo. These data suggest that the disinhibitory effect of CXCL12 towards myelin may be a useful feature to facilitate optic nerve regeneration, particularly in combination with other axon growth stimulatory treatments.